(untitled) (Research, Society and Development, 2021)
With population growth, there is an increase in demand for food, making irrigation an important technology for this purpose. Therefore, the planning and technical knowledge of environmental variables are essential for the implementation of irrigation, facilitated by geoprocessing techniques, and can help in decision making, mainly due to the ability and ease of working large areas. This work aimed to identify the areas with aptitude for the implementation of irrigation systems by central pivot in the municipality of Lagoa Grande - MG. Data from Mapbiomas, IDE-Sisema and USGS were used, using geoprocessing techniques, observing technical and legal restrictions, and applying weighted data overlap. As a result, it was found that the municipality has 7.9% of its area irrigated by central pivot. In a general analysis, the municipality has 71.58%of its area with some aptitude for the expansion of irrigated agriculture via central pivot. The spatial analysis tools through the GIS proved to be efficient in the manipulation and integration of the data used to identify and quantify the areas suitable for the implementation of a central pivot irrigation system, which can be a viable alternative for decision-making.